Deletion of fibroblast activation protein provides atheroprotection. Issue 4 (13th May 2020) - Stein, Sokrates; Weber, Julien; Nusser-Stein, Stefanie; Pahla, Jürgen; Zhang, Hui E; Mohammed, Shafeeq A; Oppi, Sara; Gaul, Daniel S; Paneni, Francesco; Tailleux, Anne; Staels, Bart; von Meyenn, Ferdinand; et al.
Abstract: Aims: Fibroblast activation protein (FAP) is upregulated at sites of tissue remodelling including chronic arthritis, solid tumours, and fibrotic hearts. It has also been associated with human coronary atherosclerotic plaques. Yet, the causal role of FAP in atherosclerosis remains unknown. To investigate the cause–effect relationship of endogenous FAP in atherogenesis, we assessed the effects of constitutive Fap deletion on plaque formation in atherosclerosis-prone apolipoprotein E ( Apoe ) or low-density lipoprotein receptor ( Ldlr ) knockout mice. Methods and results: Using en face analyses of thoraco-abdominal aortae and aortic sinus cross-sections, we demonstrate that Fap deficiency decreased plaque formation in two atherosclerotic mouse models (−46% in Apoe and −34% in Ldlr knockout mice). As a surrogate of plaque vulnerability fibrous cap thickness was used; it was increased in Fap -deficient mice, whereas Sirius red staining demonstrated that total collagen content remained unchanged. Using polarized light, atherosclerotic lesions from Fap -deficient mice displayed increased FAP targets in terms of enhanced collagen birefringence in plaques and increased pre-COL3A1 expression in aortic lysates. Analyses of the Stockholm Atherosclerosis Gene Expression data revealed that FAP expression was increased in human atherosclerotic compared to non-atherosclerotic arteries. Conclusions: Our data provide causal evidence that constitutive Fap deletion decreases progression of experimental atherosclerosis and increases features of plaque stability with decreased collagen breakdown. Thus, inhibition of FAP expression or activity may not only represent a promising therapeutic target in atherosclerosis but appears safe at the experimental level for FAP-targeted cancer therapies. Graphical Abstract: